Green Economy as a Mechanism of Sustainable Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In world practice, special importance is attached to the sustainable development of regions, the study of their economic and ecological systems in mutually effective harmony. In particular, the development of countries directly depends on the stability of regions, and the positive aspects of this issue include the rational and effective use of resources based on the expansion of the innovative economy. The article describes the need and importance of the transition to a green economy, the structure of the green economy and its important features, its importance in the development of countries and in ensuring the stability of economic growth. The production of renewable energy sources, reduction of carbon emissions, and ensuring energy efficiency are discussed in detail.